(untitled) (Journal of Kathmandu Medical College, 2018)
Background: Lower gastrointestinal endoscopy requires adequate bowel preparation. However there is no unanimous recommendation on choice of agent of bowel preparation for the purpose of screening flexible sigmoidoscopy. Objective: To compare the quality of bowel preparation and patient’s tolerance between Enema (Solution of Glycerin 15% w/v and Sodium Chloride 15% w/v)and Polyethylene glycol for screening flexible sigmoidoscopy. Methodology: All consecutive patients undergoing screening flexible sigmoidoscopy were included in the study. We prospectively divided the patients into two groups. Group A received per rectal enema and group B received oral bowel preparation with polyethylene glycol. Adequacy of bowel preparation and patient’s tolerance between two groups was graded. Data were analysed using Microsoft Excel 2010. Results: Results were comparable regarding quality of bowel preparation between two groups (A and B), excellent in 20% and 33.33% and good in 60% and 50% respectively. Almost all patients could tolerate the preparation agent in Group A (n=28). In-group B, eight patients (26.66%) considered the oral preparation agent difficult to tolerate and two patients (6%) were unable to complete the preparation. Conclusion: Enema (Solution of Glycerin 15% w/v and Sodium Chloride 15% w/v) and Polyethylene glycol have similar quality of bowel preparation and for screening sigmoidos copy. Enema is adequate and much easily tolerable compared to polyethylene glycol. Journal of Kathmandu Medical College, Vol. 7, No. 2, Issue 24, Apr.-Jun., 2018, page: 50-54